2022
DOI: 10.3389/fimmu.2022.874605
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of STING in Insect Innate Immune Responses and Pathogen Evasion Strategies

Abstract: Emerging evidence reveals that the stimulator of the interferon genes (STING) signaling pathway in insects and other animal cells helps them to sense and effectively respond to infection caused by numerous types of microbial pathogens. Recent studies have shown that genomic material from microbial pathogens induces the STING signaling pathway for the production of immune factors to attenuate infection. In contrast, microbial pathogens are equipped with various factors that assist them in evading the STING sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Cytosolic nucleic acid sensors serve as critical elements of innate immunity in many different organisms, reviewed in [ 86 ]. In mammalian cells, two of the aforementioned SMA modifiers (CORO1C and ZPR1) have been implicated in R-loop resolution and the subsequent DNA-damage response [ 87 89 ], both of which fall into the general category of DAMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic nucleic acid sensors serve as critical elements of innate immunity in many different organisms, reviewed in [ 86 ]. In mammalian cells, two of the aforementioned SMA modifiers (CORO1C and ZPR1) have been implicated in R-loop resolution and the subsequent DNA-damage response [ 87 89 ], both of which fall into the general category of DAMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Gliomas reside in the brain and were previously thought to be immunologically privileged and immune surveillance spared, but recent studies have shown that the brain is an active regulatory point of immune surveillance. 57,60 Without disruption of the BBB, the infiltration of peripheral immune cells into gliomas is very limited. However, when the BBB is disrupted by tumor growth or inflammation, gliomas are infiltrated by immunosuppressive cells.…”
Section: Mechanisms Of Chemotherapy Resistance In Gliomamentioning
confidence: 99%
“…Researchers have been able to identify novel circRNAs by revising or discovering existing ones in recent years as the depth of sequencing platforms has increased. CircRNAs of insects are involved in various aspects of insect biology, including development [ 63 ], reproduction [ 64 , 65 ], metamorphosis [ 66 , 67 ], insecticide resistance, aging [ 68 ], life-span [ 69 ], and host–pathogen interactions and immunity [ 70 , 71 ], among others ( Figure 2 ). These potential functions imply that they could be key regulators of insect physiological functions.…”
Section: Circrnas In Insectsmentioning
confidence: 99%